Logos, Mythos, Stauros - Ricoeur, Paul (Philosophy & theology, 2004)
In Etre, Monde, Imaginaire, Breton attempts to overcome the familiar opposition between being and world and, within the former, between mythos and logos. In The Word and the Cross, he refuses an opposition between the Pauline theology of the Cross and the Johanine theology of the Word. The success of these three moves depends on Breton’s claim for a Nothing that transcends both determination and reflection, as well as the contradictions that presuppose them.